Upper cervical spine trauma in Niamey: A 3-Year retrospective analysis of 27 cases - Murhega, Roméo Bujiriri; Ibrahim, Assoumane Issa; Nana Rachida, IBN HALID; Kelani, Aminath (Interdisciplinary neurosurgery : Advanced techniques and case management, 2025)
•Upper cervical spine injuries predominantly affect young adults in Niger.•C2 fractures, especially Type II odontoid, were the most common lesions.•Motorcycle accidents were the leading cause of cervical trauma (55.6%).•Posterior C1–C2 fixation was the preferred surgical technique in 45% of cases.•Study highlights challenges and adaptations in low-resource neurosurgical settings. Traumatic injuries of the upper cervical spine are complex and often life-threatening. This study presents novel insights into the clinical, radiological, and therapeutic characteristics of upper cervical trauma cases managed in Niamey, Republic of Niger. We conducted a retrospective descriptive study involving 27 patients admitted for upper cervical spine trauma between January 1, 2020, and March 31, 2023. All patients underwent CT imaging, and MRI was used selectively. Fracture classification was validated by two independent neurosurgeons. Statistical analyses were performed using JAMOVI 2.3.28.0. The cohort had a mean age of 33.9 ± 15.4 years; 51.9 % were under 30 years old. Motorcycle accidents were the leading cause (55.6 %). Neurological deficits were observed in 33.3 %, and 66.6 % were ASIA grade E. C2 injuries predominated (70.4 %), primarily odontoid fractures (81.8 %) with 33.3 % being Anderson and Alonzo type II with a horizontal fracture line. Surgical treatment was indicated in 74.1 % of cases. The Harms technique was the most used method (30 %). C2 Type II odontoid fractures are the most frequent pattern in upper cervical trauma in Niamey. Despite limited resources, surgical stabilization is feasible and necessary. These findings highlight the need for strengthened road safety and improved diagnostic access in sub-Saharan settings.